The HIV-1 epidemic in Bolivia is dominated by subtype B and CRF12_BF “family” strains - Guimarães, Monick L. (2012)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de AIDS e Imunologia Molecular. Rio de Janeiro, RJ, Brasil.